Unnecessary interruptions of cardiac massage during simulated cardiac arrests - Marsch, Stephan; Tschan, Franziska; Semmer, Norbert; Spychiger, Martin; Breuer, Marc; Hunziker, Patrick (My University, 2005)
Background and objective: Cardiopulmonary resuscitation should not be interrupted until the return of spontaneous circulation or the decision to withhold further treatment. There are no data on how consistent in-hospital cardiopulmonary resuscitation is performed. Accordingly, the aim of the present study was to identify length and type of unnecessary interruptions in simulated cardiac arrests. Methods: The study was carried out in a patient simulator. A scenario of cardiac arrest due to ventricular fibrillation was used. Resuscitation teams consisted of three nurses, a resident and a staff physician. Using videotapes recorded during simulations, the activities of the teams were coded in 5-s intervals. Unnecessary interruptions were defined as any interruptions in cardiac massage of 10s or more that were not caused by defibrillation or endotracheal intubation. Results: Twelve teams were studied. The total time of possible cardiac massage was 414 +/- 125 s. In each team at least one unnecessary interruption occurred (range 1-5). Interruptions mounted up to 65 +/- 40 s (range 20-155) or 16 +/- 10% (range 5-41) of the total time of possible cardiac massage. Failure to swiftly resume cardiac massage after an unsuccessful defibrillation accounted for 14 of 39 episodes and for 44 +/- 40% of the time of unnecessary interruptions. The debriefings revealed that participants had generally not noticed the unnecessary interruptions during the simulation. Conclusions: The present study identified a significant amount of unnecessary interruptions in cardiac massage. These interruptions were not noticed by the health-care workers involved.
Keywords: resuscitation; cardiopulmonary resuscitation; heart massage; advanced; life support; teaching; patient simulation; CARDIOPULMONARY-RESUSCITATION; PRECORDIAL COMPRESSION